Biosynthesized Iron Oxide Nanoparticles from Petroselinum crispum Leaf Extract Mitigate Lead-Acetate-Induced Anemia in Male Albino Rats: Hematological, Biochemical and Histopathological Features - Sabry M. El-Bahr; Amal M. Elbakery; Nashwa El-Gazzar; Aziza A. Amin; Saad Al-Sultan; Mohammed A. Alfattah; Saad Shousha; Sameer Alhojaily; Mohammad Shathele; Islam I. Sabeq; Ahlam F. Hamouda (Toxics, 2021)
This study aimed to investigate the ameliorative effects of iron oxide nanoparticles (IONPs) prepared from leaf extract of Petroselinum crispum compared to those prepared using a chemical method in lead-acetate-induced anemic rats. Twenty rats were divided into four groups (five rats each). Throughout the experimental period (8 weeks), the rats in group 1 were not given any therapy. The rats in groups 2, 3 and 4 were given 400 ppm lead acetate orally for 2 weeks to make them anemic. Following that, these rats were either left untreated, given 27 ppm of chemical IONPs orally or given 27 ppm of natural IONPs orally for the remaining 6 weeks of the experiment. TEM analysis indicated that the chemically and naturally prepared IONPs had sizes of 6.22–9.7  and 64–68 nm, respectively. Serum ferritin and iron concentrations were reduced, whereas the total iron-binding capacity (TIBC), ALT, AST, urea and creatinine were significantly increased in the non-treated lead-acetate-induced anemic rats compared to those of the control. In addition, congestion, hemorrhage, necrosis, vacuolation and leukocytic infiltration in the kidneys, liver and spleen were observed in non-treated lead-acetate-induced anemic rats compared to the control. The effects of lead acetate were mitigated by IONPs, particularly the natural one. In conclusion, IONPs produced from Petroselinum crispum leaf extract can be used as an efficient and safe therapy in lead-acetate-induced anemic rats.